2006
DOI: 10.1021/es0608085
|View full text |Cite
|
Sign up to set email alerts
|

Humic Substances in Soils:  Are They Really Chemically Distinct?

Abstract: Humic substances (HS) are an operationally defined fraction of soil organic matter, and they represent the largest pool of recalcitrant organic carbon in the terrestrial environment. It has traditionally been thought that extractable HS consist of novel categories of cross-linked macromolecular structures. In this study, advanced nuclear magnetic resonance approaches were used to study the major components (proteins, carbohydrates, aliphatic biopolymers, and lignin) that are known to be present in HS, and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
220
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(242 citation statements)
references
References 31 publications
11
220
3
1
Order By: Relevance
“…Such supramolecular associations may form through relatively weak intermolecular interactions, such as hydrophobic interactions or H bonds (Sutton and Sposito, 2005). This concept is supported by recent investigations of Kelleher and Simpson (2006) who were able to assign nearly all of the NMR signals in traditional fractions of humic substances to intact or degrading biopolymers and therefore conclude that humic substances are not chemically distinct, but a complex mixture of microbial and plant biopolymers.…”
Section: Ekschmittmentioning
confidence: 76%
See 1 more Smart Citation
“…Such supramolecular associations may form through relatively weak intermolecular interactions, such as hydrophobic interactions or H bonds (Sutton and Sposito, 2005). This concept is supported by recent investigations of Kelleher and Simpson (2006) who were able to assign nearly all of the NMR signals in traditional fractions of humic substances to intact or degrading biopolymers and therefore conclude that humic substances are not chemically distinct, but a complex mixture of microbial and plant biopolymers.…”
Section: Ekschmittmentioning
confidence: 76%
“…Physical protection of SOM through occlusion within aggregates or small pores and chemical protection through interaction with mineral surfaces or with other organic molecules are considered as important mechanisms to reduce the bioavailability and accessibility of organic matter (OM) for soil microorganisms and soil enzymes (Sollins et al, 1996;Kelleher and Simpson, 2006;von Lützow et al, 2006;Bachmann et al, 2008, this issue, pp. 14-26).…”
Section: Introductionmentioning
confidence: 99%
“…It has traditionally been thought that HS consist of novel categories of cross-linked macromolecular structures that form a distinct class of chemical compounds (Stevenson, 1994). In contrast to traditional thinking however, it was recently concluded that the vast majority of humic material in soils is a very complex mixture of microbial and plant biopolymers and their degradation products, and not a distinct chemical category as is traditionally thought (Kelleher and Simpson, 2006). Furthermore, the concept that extractable SOM is comprised mainly of humic materials has also been challenged and it has been shown that the presence of organic material sourced to microbes (as extant organisms or necromass) far exceeds presently accepted values, with large contributions of microbial peptides/ proteins found in the HS fraction (Kögel-Knabner, 2002;Kiem and Kögel-Knabner, 2003;Kindler et al, 2006;Simpson et al, 2007;Potthoff et al, 2008).…”
Section: Introductionmentioning
confidence: 88%
“…This view of carbon reactivity implies that recharge of anthropogenic waste fuels microbial reduction in As-rich aquifers, even if the amount of young carbon is small compared with other pools and difficult to detect. However, recent direct observations indicate the OC in the subsurface exists in smaller, simpler molecular structures than originally thought based on bulk extractions, and that often these reactive molecules persist in sedimentary systems much longer than previously believed (10,11). This different perspective suggests that the molecular properties do not in themselves control reaction rates but OC decomposition rates are affected by ecosystem properties such as nutrient limitation, energy scarcity, or carbon bioavailability due to physical limitation such as reactions with mineral surfaces (12)(13)(14).…”
mentioning
confidence: 88%